A New Staging System Based on the Dynamic Prognostic Nomogram for Elderly Patients With Primary Gastrointestinal Diffuse Large B-Cell Lymphoma - Wang, Junmin; Ren, Weirui; Zhang, Chuang; Wang, Xiaoya (Frontiers in Medicine, 2022)
Objective: The purpose of this study is to establish an accurate prognostic model based on important clinical parameters to predict the overall survival (OS) of elderly patients with primary gastrointestinal diffuse large B-cell lymphoma (EGI DLBCL). Method: The Cox regression analysis based on data from the Surveillance, Epidemiology, and End Results (SEER) database. Results: Totally 1783 EGI DLBCL cases were eligible for the study (median [interquartile range, IQR] age, 75 [68-82] years; 974 [54.63%] males), of which 1248 were randomly assigned to the development cohort, while 535 were into the validation cohort. A more accurate and convenient dynamic prognostic nomogram based on age, stage,radiation and chemotherapy were developed and validated, of which the predictive performance was superior to that of Ann Arbor staging system(C-index: 0.69 [95% CI: 0.67-0.71] vs 0.56 [95%CI: 0.54-0.58]; P＜0.001). The 3-year and 5-year ROC curves of the nomogram in the development cohort and the validation cohort with a single multivariate meaningful variable at specific time points. Conclusion: We establish and validate a more accurate and convenient dynamic prognostic nomogram for patients with EGI DLBCL,which can can provide evidence for individual treatment and follow-up.